PEMANFAATAN MEDIA SOSIAL DALAM EDUKASI WAKAF DI KOTA MEDAN: PELUANG LITERASI DIGITAL DAN TANTANGANNYA - Yusnita; Fitri Yani (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2026)
This study explores the implementation of social media as a tool for waqf education in the digital era. The increasing use of digital platforms among the younger generation presents opportunities and challenges for Islamic philanthropic institutions, particularly in enhancing public literacy regarding waqf. Using a descriptive qualitative method, data were collected through interviews with waqf practitioners (nazhir), academics, and social media users in Medan. The findings reveal that while social media offers significant potential for educational outreach—such as wide accessibility, interactive content, and visual appeal—its use remains suboptimal. This is due to limited digital resources, lack of strategic content planning, and insufficient collaboration between stakeholders. The study emphasizes the need for professional digital teams, credible content development, and partnerships with Islamic digital influencers. These findings contribute to the discourse on digital Islamic philanthropy and offer practical implications for strengthening waqf literacy in Indonesia.